Radiocarbon Analysis of Modern Skeletal Remains to Determine Year of Birth and Death—A Case Study. Issue 3 (2015) - Cook, G T; Ainscough, L A N; Dunbar, E
Abstract : To aid in the development of a biological profile for human remains found in Collyhurst (Manchester, England), we undertook radiocarbon analysis of tooth enamel, tooth collagen, and bone collagen on behalf of the Greater Manchester Police. On the basis of the analyses of the teeth, we concluded that the person was born between 1950 and 1954, while on the basis of our analyses of cortical and trabecular bone we estimated the year of death to be between 1969 and 1974. This would make the maximum age range around 15 to 24 yr. Analyses of the dentition and other skeletal parameters can eliminate the younger part of the range, so an age of around 18 to 24 yr at death would seem most likely. The δ 13 C and δ 15 N values for the bone collagen were higher than would be expected for someone subsisting on a purely terrestrial diet, implying some consumption of marine resources, which could lead to reduced 14 C activities. Taking any potential marine effect into account could reduce this age range to around 18 to 21 yr.